Prevalence of pre-diabetes in adults aged 25 – 45 years in a Durban-based clinical setting, South Africa: A retrospective study - Sosibo, Aubrey M.; Mzimela, Nomusa C.; Ngubane, Phikelelani S.; Khathi, Andile (Primary care diabetes, 2023)
Due to pre-diabetes being underexplored, its prevalence was investigated in study participants aged 25–45 years in a Durban-based tertiary-level clinical setting in South Africa. The study was done using a retrospective study design. Fasting blood samples from consented patients with no previous diagnosis of diabetes and within the specified age range were collected from King Edward Hospital in Durban. The pre-diabetes diagnosis was confirmed in participants with fasting glucose concentrations between 5.6 and 6.9 mmol/L and glycated haemoglobin (HbA1c) levels between 5.7 % and 6.4 % using the American Diabetes Association (ADA) and World Health Organisation (WHO) diagnosis criteria. The study participants' characterisation was stratified according to the diagnosis criterion, age, gender and ethnicity. An alarming 68 % average pre-diabetes prevalence across ADA and WHO criteria in the Durban, eThekwini district sample population. The highest prevalence was recorded using the IFG criterion (83%) and the lowest when using the HbA1c criterion (54 %). Between the White, Black and Indian ethnic groups, the Indian group were more predisposed to pre-diabetes onset, with a prevalence of 62.7 %. If pre-diabetes management is unattended, an unprecedented increase in metabolic disorders such as Type 2 Diabetes Mellitus (T2DM) and all-cause mortality incidence can be expected. Therefore, the study reveals a window of opportunity to intensify preventative measures and mitigate the incidence of T2DM. •Findings show a disturbingly high number (68 %) of study participants with pre-diabetes.•Study participants from the Indian ethnic group appeared to be more predisposed to developing pre-diabetes.•Men are more likely to develop pre-diabetes than females.•The study suggests increasing preventative measures in the population to prevent a conceivably overwhelming incidence of T2DM.